Improving the likelihood of positive outcomes for survivors of sexual violence, considering intersections between justice, gender, and trauma - Bond, Kim; Davis, Kate (Wiley, 2025)
This paper explores the complex impacts of childhood abuse on survivors, emphasising how these experiences shape both individual and societal outcomes. It acknowledges the extensive and enduring effects of abuse, which extend beyond immediate physical and psychological harm to broader social and economic repercussions. The paper critically examines the difficulties of holding perpetrators accountable within the criminal justice system, where low reporting rates, high attrition, and re‐traumatization are significant challenges. Using a gendered lens, the analysis situates these issues within a broader social, cultural, and historical context, highlighting how abuse, particularly sexual abuse, is perceived and managed. A key focus is on the issue of disclosure, essential for survivors to access support and justice. However, disclosure is often hindered by fears of disbelief, stigma, and retaliation, which are exacerbated by socioeconomic factors. Even when support systems are available, low conviction rates and ongoing re‐victimisation significantly impede justice and healing, undermining the criminal justice system and support structures. The paper also discusses the wider implications of childhood abuse for public health, social services, and education. The trauma affects not only survivors' mental and physical health but also their ability to engage fully in society, impacting relationships, employment, and educational outcomes. These personal challenges lead to broader societal costs, including increased demand for healthcare and lost productivity. The paper advocates for an integrated approach that improves prevention, enhances safeguarding, and develops effective support systems, addressing both the immediate needs of survivors and systemic barriers to recovery and justice.
Keywords: Political Science & Public Administration; 4407 Policy and administration; 4409 Social work; 4410 Sociology